Licochalcone A inhibits EGFR signalling and translationally suppresses survivin expression in human cancer cells. Issue 2 (27th November 2020) - Gao, Feng; Li, Ming; Yu, Xinfang; Liu, Wenbin; Zhou, Li; Li, Wei
Abstract: Dysfunction of epidermal growth factor receptor (EGFR) signalling plays a critical role in the oncogenesis of non–small‐cell lung cancer (NSCLC). Here, we reported the natural product, licochalcone A, exhibited a profound anti‐tumour efficacy through directly targeting EGFR signalling. Licochalcone A inhibited in vitro cell growth, colony formation and in vivo tumour growth of either wild‐type (WT) or activating mutation EGFR‐expressed NSCLC cells. Licochalcone A bound with L858R single‐site mutation, exon 19 deletion, L858R/T790M mutation and WT EGFR ex vivo, and impaired EGFR kinase activity both in vitro and in NSCLC cells. The in silico docking study further indicated that licochalcone A interacted with both WT and mutant EGFRs. Moreover, licochalcone A induced apoptosis and decreased survivin protein robustly in NSCLC cells. Mechanistically, we found that treatment with licochalcone A translationally suppressed survivin through inhibiting EGFR downstream kinases ERK1/2 and Akt. Depletion of the translation initiation complex by eIF4E knockdown effectively inhibited survivin expression. In contrast, knockdown of 4E‐BP1 showed the opposite effect and dramatically enhanced survivin protein level. Overall, our data indicate that targeting survivin might be an alternative strategy to sensitize EGFR‐targeted therapy.